Islamic Fintech Platforms for Financial Inclusion: Case Study on Digital Banking in Rural Communities - Takim Mulyanto; Sarah Williams; David Martin (Journal Markcount Finance, 2025)
Financial inclusion remains a critical challenge in rural communities where geographical barriers, limited infrastructure, and socio-cultural factors restrict access to formal financial services. Islamic fintech platforms have emerged as an alternative digital solution that combines technological innovation with Sharia-compliant financial principles, offering potential pathways for inclusive finance. The objective of this study is to examine how Islamic fintech-based digital banking platforms contribute to financial inclusion in rural communities through an in-depth case study approach. A qualitative research design was employed, involving purposive sampling of rural digital banking users, community leaders, fintech service providers, and institutional stakeholders. Data were collected through semi-structured interviews, field observations, and document analysis, and were analyzed thematically to capture patterns of access, usage, trust, and perceived benefits. The findings reveal that Islamic digital banking platforms significantly improve account ownership, transaction frequency, access to savings and microfinance, and user confidence in formal financial institutions. Adoption is strongly influenced by Sharia compliance, digital literacy, proximity to agent networks, and endorsement from local religious and community institutions. The study concludes that Islamic fintech platforms function not only as technological tools but also as socially embedded financial instruments that align ethical values with digital innovation. The novelty of this research lies in its integration of Islamic economic theory with empirical rural fintech analysis, demonstrating how value-based digital banking can effectively advance financial inclusion in underserved rural contexts.